Organic Fertilizer Training Using Animal Waste to Enhance Sustainable Agriculture in Jubung Village - Harsanti, Restiani Sih; Indri Fariroh; Usmadi; Slameto; Sundahri; Arfiane Desthariani; Firman Aritonang (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
This community service program aimed to address the stagnant rice production and the high cost of inorganic fertilizers in Jubung Village, Sukorambi District, Jember Regency, by introducing organic fertilizer production using agricultural waste and livestock manure activated with MOL (local microorganisms) derived from roots. The program was implemented through several stages: socialization, counseling on the role of organic materials in improving soil fertility, practical training in producing organic fertilizers, and program monitoring and evaluation. The training involved members of the “Tani Mulyo” farmer group, who showed high enthusiasm and active participation. As a result, farmers gained knowledge and skills in processing organic waste into organic fertilizers, thereby reducing their dependence on inorganic fertilizers and promoting sustainable agricultural practices. The fermentation process successfully produced organic fertilizers with desirable characteristics: a crumbly texture, a dark brown color, and no pungent odor, indicating the effectiveness of MOL from roots as a bioactivator. This initiative is expected to support environmentally friendly agriculture and increase rice productivity in the area.